An investigation of the inhibitive capability of synthesized thiosemicarbazides on the corrosion of carbon steel in acid solutions - Quraishi M.A.; Sardar R.; Khan S. (My University, 2025)
Purpose - This paper mainly aims to study the influence of some thiosemicarbazides, namely, 1-hydroxyphenyl-4-phenyl thiosemicarbazide (HPT), 1,4-diphenyl thiosemicarbazide (DPT), 1-aminophenyl-4-phenyl thiosemicarbazide (APT) and 1-cinnamyl-4-phenyl thiosemicarbazide (CPT) on the corrosion inhibition of carbon steel in hydrochloric and sulphuric acid. Design/methodology/approach - All inhibition experiments were conducted on carbon steel in 1N HCl and 1N H2SO4 solution. Weight loss experiments were carried out according to the ASTM standard procedure. Polarization studies were carried out in a three-electrode cell assembly connected to an EG&G Princeton applied research potentiostat/galvanostat (model 173). Findings - For all the compounds a consistent trend of increase in inhibition efficiency was observed as a function of inhibitor concentration. The adsorption of all the compounds on to the carbon steel surface in the acidic solution was found to obey the Tempkin's adsorption isotherm. The values of activation energy and free energy of adsorption for all the compounds were also calculated. Polarization measurement revealed that the studied thiosemicarbazides act predominantly as mixed inhibitors in both the acid solutions, with the exception of DPT, which predominantly behaved as a cathodic inhibitor in 1N HCl. Research limitations/implications - These inhibitors could have application in industries, where hydrochloric and sulphuric acid solution are used to remove scale and salts from steel surfaces, such as acid cleaning of tankage and pipeline, and may render dismantling unnecessary. Originality/value - This paper reveals that thiosemicarbazides can be successfully used for protection of carbon steel corrosion in acid solutions. © Emerald Group Publishing Limited.